British science fiction cinema - Hunter, I. Q., 1964- (British popular cinema., 1999)
British Science Fiction Cinema is the first substantial study of a genre which, despite a sometimes troubled history, has produced some of the best British films, from the prewar classic Things to Come to Alien made in Britain by a British director. The contributors to this rich and provocative collection explore the diverse strangeness of British science fiction, from literary adaptions like Nineteen Eighty-Four and A Clockwork Orange to pulp fantasies and 'creature features' far removed from the acceptable face of British cinema. Through case studies of key films like The Day the Earth Caught Fire , contributors explore the unique themes and concerns of British science fiction, from the postwar boom years to more recent productions like Hardware , and examine how science fiction cinema drew on a variety of sources, from TV adaptions like Doctor Who and the Daleks , to the horror/sf crossovers produced from John Wyndham's cult novels The Day of the Triffids and The Midwich Cuckoos (filmed as Village of the Damned ). How did budget restrictions encourage the use of the 'invasion narrative' in the 1950s films? And how did films such as Unearthly Stranger and Invasion reflect fears about the decline of Britain's economic and colonial power and the 'threat' of female sexuality? British Science Fiction Cinema celebrates the breadth and continuing vitality of British sf film-making, in both big-budget productions such as Brazil and Event Horizon and cult exploitation movies like Inseminoid and Lifeforce .